Analysis of mismatch after ball screens in Spanish professional basketball - Calvo, J. L.; Menéndez Garcia, A.; Navandar, A. (International Journal of Performance Analysis in Sport, 2017)
In basketball, the ball screen has been described as one of the most important and successful forms of finishing a play, and this could generate a mismatch when defenders in a man-to-man defensive setup switch their assigned markers. This study aimed to determine (1) which players benefit the most in the case of a mismatch and (2) how does the duration of action affect the mismatch. A total of 698 situations of mismatch after ball screens from 40 matches of the 2015-2016 regular season of the male Spanish professional Basketball League (ACB) were quantitatively analysed. The results found that although inside players were the ones who finished the action more often, the duration was a crucial factor. An action that lasted under five seconds favoured the offence, with the outside players benefitting the most in such a situation. However, if the offence failed to finish the action in the first four seconds, the mismatch favoured the defence, as they had more time to organise themselves to counter the threats posed by the offence. Thus, the mismatch can be used as an effective defensive strategy, if cleverly executed.